The Effects of Age, Endometriosis, Polycystic Ovarium Syndrome, and Obesity on the Success of Embryo Transfer on In Vitro Fertilization - Hafiizha, Atthahira Amalia; Budihastuti, Uki Retno; Murti, Bhisma (Journal of Maternal and Child Health, 2021)
Background: One of the important stages in in vitro fertilization (IVF) success is the embryo transfer (ET). Many studies are examining the effect of maternal factors on in vitro fertiliza